2013
DOI: 10.1093/mnras/stt2023
|View full text |Cite
|
Sign up to set email alerts
|

A dichotomy in satellite quenching around L* galaxies

Abstract: We examine the star formation properties of bright (∼ 0.1 L * ) satellites around isolated ∼ L * hosts in the local Universe using spectroscopically confirmed systems in the Sloan Digital Sky Survey DR7. Our selection method is carefully designed with the aid of N -body simulations to avoid groups and clusters. We find that satellites are significantly more likely to be quenched than a stellar mass-matched sample of isolated galaxies. Remarkably, this quenching occurs only for satellites of hosts that are them… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
78
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 81 publications
13
78
2
Order By: Relevance
“…While they have the highest low-mass passive fraction of all of our environmental metrics, this fraction is still lower than previous SDSS-based work. At 8.0<log 10 [M * /M ] < 9.0, Phillips et al (2014), Geha et al (2012) and Wheeler et al (2014) find a passive fraction of ∼20-30 per cent (albeit from the same sample), while we find ∼10-20 per cent. This difference could either be due to sample selection (our passive selection based on H α sSFR may be more stringent than their H α EW selection) or a difference in stellar mass estimations.…”
Section: Pa S S I V E F R Ac T I O N S O F G a L A X I E S A S A F U contrasting
confidence: 40%
See 2 more Smart Citations
“…While they have the highest low-mass passive fraction of all of our environmental metrics, this fraction is still lower than previous SDSS-based work. At 8.0<log 10 [M * /M ] < 9.0, Phillips et al (2014), Geha et al (2012) and Wheeler et al (2014) find a passive fraction of ∼20-30 per cent (albeit from the same sample), while we find ∼10-20 per cent. This difference could either be due to sample selection (our passive selection based on H α sSFR may be more stringent than their H α EW selection) or a difference in stellar mass estimations.…”
Section: Pa S S I V E F R Ac T I O N S O F G a L A X I E S A S A F U contrasting
confidence: 40%
“…Phillips et al (2014) find that satellite galaxies are much more likely to be quenched if their host galaxy is also passive. As such, the same environmental effects may drive passive evolution in both centrals and satellites (i.e.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…While the stel-lar mass or surface mass density of a galaxy may be more closely connected to quenching for massive systems (Peng et al 2010;Cheung et al 2012;Woo et al 2013), recent work has shown that environment is likely the dominant driver of quenching at the lowest mass scales (M < 10 9 M , Geha et al 2012). For example, studies comparing satellite galaxies to isolated field systems of similar stellar mass in the local Universe find that satellites tend to exhibit lower star formation rates, more bulge-dominated morphologies, as well as older and more metal-rich stellar populations (Baldry et al 2006;van den Bosch et al 2008;Cooper et al 2010b;Pasquali et al 2010;Tollerud et al 2011;Phillips et al 2014). This observed suppression of star formation in satellite galaxies is commonly referred to as "environmental quenching".…”
Section: Introductionmentioning
confidence: 99%
“…However, the environmental quenching of dwarfs is far from ubiquitous (e.g. Phillips et al 2014Phillips et al , 2015Wheeler et al 2014). …”
Section: Introductionmentioning
confidence: 99%